China’s Push for Greater Influence in the Popular Culture Arena: The Ip Man Saga - Aukia Jukka (Taylor & Francis, 2022)
This article offers a critical analysis of four kung fu films that were co-produced by Hong Kong and Mainland China and depict the legend of Ip Man, Bruce Lee’s teacher. It discusses different representations in the Ip Man saga, and argues that while othering Japan and the West, the Chinese self is depicted in the saga as a benevolent but powerful actor. The texts of the films are thus found to echo past and present Mainland identity narratives and to be connected to the Mainland’s push for soft power. The article links popular culture to politics by showing how political narratives are made attractive at an everyday level, thus contributing to the literature on identity and soft power.